A Holistic Approach to Improve Nursing Retention During the First Year of Employment. Issue 3 (July 2016) - Bonczek, Mary Ellen; Quinlan-Colwell, Ann; Tran, Stephanie; Wines, Kathy
Abstract : The national nursing shortage, coupled with our country's financial challenges, provides a platform for creative nursing retention practices by health care organizations. It was from that platform that this research study was undertaken to determine if nurses who receive a high level of personal interest, education, and support through self-care workshops and one-on-one communication would continue their employment at the organization. The research question was "Will providing holistic self-care workshops during the first year of employment impact the nursing retention rates?" A total of 89 newly hired nurses were enrolled in the study, in which they participated in a 90-minute interactive workshop held weekly for 4 consecutive weeks. In the workshops, the nurses were guided to an understanding of the importance of self-care activities. The responses of the nurses who participated were positive. As a result of this study, the self-care workshops have continued with modification in length and the time when they were provided.